The Effects of Apelin and Elabela Ligands on Apelin Receptor Distinct Signaling Profiles - Jiang, Yunlu; Yan, Maocai; Wang, Chunmei; Wang, Qinqin; Chen, Xiaoyu; Zhang, Rumin; Wan, Lei; Ji, Bingyuan; Dong, Bo; Wang, Huiyun; Chen, Jing (Frontiers in Pharmacology, 2021)
Apelin and Elabela are endogenous peptide ligands for Apelin receptor (APJ), a widely expressed G protein-coupled receptor. They constitute a spatiotemporal dual ligand system to control APJ signal transduction and function. We investigated the effects of Apelin-13, pGlu1-apelin-13, Apelin-17, Apelin-36, Elabela-21 and Elabela-32 peptides on APJ signal transduction. Whether different ligands are biased to different APJ mediated signal transduction pathways was studied. We observed the different changes of G protein dependent and β-arrestin dependent signaling pathways after APJ was activated by six peptide ligands. We demonstrated that stimulation with APJ ligands resulted in dose-dependent increases in both G protein dependent [cyclic AMP (cAMP) , Ca2+ mobilization, and the early phase extracellular related kinase (ERK) activation ] and β-arrestin dependent [GRKs, β-arrestin 1, β-arrestin 2, and β2 subunit of the clathrin adaptor AP2] signaling pathways. However, the ligands exhibited distinct signaling profiles. Elabela-32 showed a >1000-fold bias to the β-statin-dependent signaling pathway. These data provide that Apelin-17 was biased towards β-arrestin dependent signaling. Eabela-21 and pGlu1-Apelin-13 exhibited very distinct activities on the G protein dependent pathway. The activity profiles of these ligands could be valuable for the development of drugs with high selectivity for specific APJ downstream signaling pathways.